Endoscopic Ultrasound-Guided Drainage in the Management of Postoperative Pancreatic Fistula After Partial Pancreatectomy - Wang, Liu; Zhang, Yin; Chen, Bingfang; Ding, Yanbo (Turkish Journal of Gastroenterology, 2021)
Background: Postoperative pancreatic fistula (POPF) is the most frequent and harmful complication following pancreatic surgery. Traditional management includes conservative treatment, percutaneous drainage (PD), and reoperation. The objective of the present study was to evaluate the safety and effectiveness of EUS (Endoscopic ultrasound)-guided drainage by using nasocystic tubes combined with single or 2 stents for POPF. Methods: Patients who had POPF after surgery and then underwent EUS-guided drainage, from October 2016 to October 2019, were enrolled in this study. Technical success was defined as successful transgastric puncture of the peripancreatic fluid collection (PFC) and deployment of the nasocystic tube and stents. Clinical success was defined as symptomatic improvement and the resolution of the fluid collection on follow-up CT scan. Results: A total of 15 patients received EUS-guided drainage. In 13 patients, a nasocystic tube was placed in the PFC combined with a double-pigtail plastic stent. In the remaining 2 patients, a nasocystic tube and 2 stents each were inserted in place. Technical success was achieved in 15 of 15 patients (100%). Clinical success was achieved in 14 of 15 patients (93.3%). In one case, the stent was blocked on the 10th day after the procedure. The median time between surgery and EUS-guided drainage was 10 (5-32) days. The median time of hospital stay after EUS-guided drainage was 16 (11-48) days. Operation-unrelated death occurred in 1 patient (7%) during follow-up. Conclusion: EUS-guided drainage with a nasocystic tube and double-pigtail stents appears to be safe and technically feasible, and could be an alternative treatment for patients with POPF.